Transformasi Administrasi Tatalaksana Sekolah di Era Digital: Tantangan dan Peluang untuk Pendidikan Masa Depan - Fatimah, Meti; Sugiyarti, Sri; Ahmada, Futiha Alambarra Amaan (TSAQOFAH, 2024)
The rapid advancement of technology due to globalization has led to digital transformation in several educational sectors, particularly in school administration. Using a literature review approach, this article aims to explore school administration management and the impact of digital transformation, as well as to identify the challenges faced and opportunities that can be leveraged to improve the quality of education. The research shows that school administration plays a crucial role in ensuring the smooth operation of schools. Digital transformation in school administration, such as the use of integrated information management systems, online learning platforms, and classroom management applications, can enhance transparency and data accuracy within schools. However, several challenges, including budget limitations, lack of technical skills, resistance to change, and data security issues, are still obstacles that need to be addressed. By understanding these aspects, educational institutions are expected to design effective strategies to integrate technology and capitalize on its potential for better educational management.